2017
DOI: 10.1080/13621718.2016.1251733
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural characteristics and mechanical properties of Al–Mg–Si alloy self-reacting friction stir welded joints

Abstract: The 5 mm thick Al-Mg-Si alloy was self-reacting friction stir welded using the specially designed tool at a constant rotation speed of 400 rev min −1 with various welding speeds. Defect-free welds were successfully obtained with welding speeds ranging from 150 to 350 mm min −1 , while pore defects were formed in the weld nugget zone (WNZ) at a welding speed of 450 mm min −1 . Band patterns were observed at the advancing side of WNZ. Grain size and distribution of the precipitated phase in different regions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Flash formation may occur due to the low viscosity of material under high temperature. The excessive flash formation is observed at the retreating side on the joint surface due to redundant heat input at a low welding speed of 150 m/min [5]. Zhou et al [10] observed excessive flash at the higher rotational speed of 600 rev min −1 due to excessive heat input with increasing rotation speed.…”
Section: Flash/chipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flash formation may occur due to the low viscosity of material under high temperature. The excessive flash formation is observed at the retreating side on the joint surface due to redundant heat input at a low welding speed of 150 m/min [5]. Zhou et al [10] observed excessive flash at the higher rotational speed of 600 rev min −1 due to excessive heat input with increasing rotation speed.…”
Section: Flash/chipsmentioning
confidence: 99%
“…Aluminium 2xxx, 6xxx, and 7xxx series are heattreatable alloys [1] and largely used in automobile, shipbuilding, rail, and aerospace industries because of their low density, higher strength, low weight, and high corrosion resistance. However, solidification cracking, losses of alloying material, porosity, high residual stresses, reduction in mechanical properties, oxidation, and requirement of multi-passes for thick section welding are some of the issues of fusion welding of these alloys [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The process has some disadvantages such as the low welding speed, heavy welding loads on the tool [4]. The enhancement in the plastic material flow have been investigated [5][6][7][8]. Mabrouk et al [9] used a mathematical model to express the heat generation during ultrasonic vibration improved friction stir welding process.…”
Section: Introductionmentioning
confidence: 99%
“…FSW process has undergone several modifications and improvements. These variations involved modifications in the tool, the machine, and the process itself [6][7][8]. As well as, integrating FSW process with a secondary energy source to provide more softening action, especially for welding hard materials [9].…”
Section: Introductionmentioning
confidence: 99%